2001
DOI: 10.1200/jco.2001.19.14.3422
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Liposome-MediatedE1AGene Transfer to Human Breast and Ovarian Cancer Cells and Its Biologic Effects: A Phase I Clinical Trial

Abstract: These results argue for the feasibility of intracavitary DCC-E1A administration, provide a clear proof of preclinical concept, and warrant phase II trials to determine the antitumor activity of the E1A gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
92
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 198 publications
(94 citation statements)
references
References 20 publications
1
92
0
1
Order By: Relevance
“…One such strategy is based on the finding that the HER2 gene can be repressed by the adenovirus E1A gene (41,42). A phase I clinical trial of E1A therapy showed that intracavitary injection of the E1A gene complexed with DC-Chol cationic liposome (DCC-E1A; Targeted Genetics Corp., Seattle, WA, USA) was accompanied by HER2 down-regulation, increased apoptosis, and reduced proliferation in patients with breast cancer (43).…”
Section: Discussionmentioning
confidence: 99%
“…One such strategy is based on the finding that the HER2 gene can be repressed by the adenovirus E1A gene (41,42). A phase I clinical trial of E1A therapy showed that intracavitary injection of the E1A gene complexed with DC-Chol cationic liposome (DCC-E1A; Targeted Genetics Corp., Seattle, WA, USA) was accompanied by HER2 down-regulation, increased apoptosis, and reduced proliferation in patients with breast cancer (43).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the adenovirus type 5 E1A is not a transforming protein and is distinct from the adenovirus type 12 E1A which alone can transform established cell lines (Lamberti and Williams, 1990). As a matter of fact, the adenovirus type 5 E1A has been reviewed as a tumor suppressor (Chinnadurai, 1992;Mymryk, 1996;Frisch, 2001) and used in the clinical trial (Hortobagyi et al, 2001). Unless otherwise speci®ed, the E1A referred in this article is the type 5 E1A.…”
Section: Introductionmentioning
confidence: 99%
“…5,10 Therefore, based on its ability to suppress both tumorigenicity and metastasis, E1A has been considered as a tumor suppressor gene 5,[11][12][13] and translated into multiple clinical trials. [14][15][16] In addition to the tumor suppressor activities, expression of the E1A gene in stably transfected normal fibroblast and human cancer cells has also been shown to increase sensitivity to the in vitro cytotoxicity of several anticancer drugs, such as etoposide and cisplatin in normal fibroblasts and sarcoma cells, Adriamycin in colon and hepatocellular carcinoma cells, Gemcitabine in hepatocellular and breast cancer cells, and paclitaxel in breast and ovarian cancers. [17][18][19][20][21][22][23][24][25][26][27] Our previous studies demonstrated that E1A can sensitize paclitaxel-induced cell killing in Her-2/neu-overexpressing cancer cells.…”
mentioning
confidence: 99%